Possibilities of Growing Artichoke (Cynara scolymus L.) in Hungary - Pestiné Nagy, Orsolya; Ombódi, Attila; Kassai, Tamás; Dimény, Judit (Acta Agraria Debreceniensis, 2002)
The domestication of choice broadening, special vegetable species offers new market possibilities in Hungary. The production of artichokes has good perspectives due to its high protein, vitamin and mineral contents and its wide usability. According to the literature, in Hungary it is worth examining the annual production technology, which has yet to be researched in our country. The basic aim of our work was to establish the annual production of artichoke in Hungary with scientific research.In the experiment, 5 Italian sorts (Valetta di Roma, Gobbo di Nizza, Violetto di Romagna, Violetto S. Francesino and Precoce di Romagna), 1 American sort (Green Globe) and 1 Egyptian sort (Balady) were used. For one half of the plants, we tried to bring on bud-production appearing in the first year only with early planting, while we used also a gibberellic acid hormone treatment for the other half.Only the sort Green Globe had yields in appropriate quantity (21.4 t/ha) and quality. The low yield and inequable quality of buds of the Italian and Egyptian sorts refers to the fact that these sorts are not applicable for annual production in Hungary. Although the gibberellic acid treatment resulted an earlier harvest, increased the equality of buds and increased the proportion of stems producing buds except for the sort Green Globe, overall it did not have a positive effect. The hormone treatment fastened the physiological processes of the plants, thereby it induced early insenescence and lignifying of the buds. The high temperatures during the bud-formation period largely increased the ratio of flabby, over-blowing buds, so the planting must be timed in the future that the harvest period is in early automn or late spring, early summer months.According to our results, globe artichoke can become a perspective culture by applying cold-resistant sorts with short growing seasons, which can be produced as annual crops without hormone treatment by the appropriate timing of bud-formation.